Politics of Pasts and Futures in (Post-)Imperial Contexts - Fahner, Sebastian 1992-; Feichtinger, Christian 1991-; Fellner, Elena; Heijden, Rogier E. M. van der 1997-; Heijden, Rogier E.M.; Jones, Rhiannon Garth; Makhlouf, Peter S.; Osipian, Alexandr; Pejić, Oliver; Strootman, Rolf; Tauber, Christine; Wu, Jialin Christina; et al. (De Gruyter Oldenbourg, 2024)
Although empires have played a decisive role in political thinking and the orientation of political goals at all times, the focus of research has so far mostly been on spatial and ideological aspects. This volume, on the other hand, offers a multi-disciplinary collection of studies that deal with the instrumentalization and ongoing impacts of perspectives on empire and their place in time. Coming from archaeology, history, art history, literary studies, and social sciences, the individual case studies discuss perceptions of imperial histories and imagined futures of empires, both in imperial and in post-imperial contexts. The transcending historical significance of the imperial ideas and ideals shows the deep and long-lasting effects of empire in landscapes, mindscapes, and social structures. The diachronic cut through all epochs from antiquity to modern times is complemented by a broad global view to deepen the temporal understanding of imperial imaginaries as well as their political implications